Domestic Investment as Key Driver of Employment in Jabodetabek: Investasi Domestik sebagai Pendorong Utama Penyerapan Tenaga Kerja di Jabodetabek - Kamilah Khumairoh; Ririt Iriani Sri Setiawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Urban agglomerations like Greater Jakarta face complex labor market challenges amidst rapid economic growth and demographic shifts. Specific Background: The region’s employment dynamics are shaped by policy instruments such as minimum wage regulations, domestic investment, and the proliferation of micro and small industries. Knowledge Gap: Prior research has rarely examined the simultaneous influence of these three variables within a unified analytical model specific to the Jabodetabek context. Aims: This study aims to analyze the effects of minimum wage, domestic investment, and the number of micro and small industries on labor absorption in the Greater Jakarta area from 2017 to 2023. Results: Using a panel data regression with the Fixed Effect Model (FEM), the findings reveal that only domestic investment significantly and positively affects labor absorption, while minimum wage and the number of micro and small industries do not show significant impacts. Novelty: The study offers a novel integrated model that captures the joint influence of three key economic variables across nine metropolitan areas. Implications: The results underscore the need for policy focus on stimulating domestic investment and enhancing the capacity of small enterprises to sustainably address urban employment challenges.Highlight : Only domestic investment has a statistically significant and positive influence on labor absorption in the Greater Jakarta (Jabodetabek) area. Minimum wage and micro-small industries do not significantly affect labor absorption, highlighting structural limitations in informal sectors. Policy recommendations emphasize boosting domestic investment and improving the quality and innovation of micro-small enterprises. Keywords : Labor Absorption, Minimum Wage, Domestic Investment, Micro and Small Industries, Jabodetabek